Implementasi Taḥfīẓ, Taḥsin dan Tadabur dalam Meningkatkan Kemampuan Menghafal Al-Qur'an pada Mahasiswa Universitas Darussalam Gontor Ponorogo - Oky Ayu Agustin; Choeroni Choeroni; Khoirul Anwar (Universitas Darussalam Gontor, 2026)
The fundamental problem in the implementation of Qur’an memorization programs in Islamic higher education institutions is that many students struggle to maintain the quality of their memorization due to inadequate foundations in Qur’anic recitation and fluctuating motivation. This study aims to analyze the implementation and impact of integrating taḥfīẓ, taḥsin, and tadabur (3T) in improving the Qur’an memorization ability of students in the Al-Qur’an and Tafsir Studies Program at Universitas Darussalam Gontor. This study employs a qualitative approach with a field research design. Data were collected through interviews, observations, and documentation involving students and lecturers or muhāfiẓ, and then analyzed using triangulation techniques. The findings show that taḥfīẓ enhances the quantity of memorization and student discipline, taḥsin improves accuracy of recitation and memorization stability, while tadabur strengthens verse comprehension and students’ intrinsic motivation. This study recommends strengthening individual mentoring, differentiating memorization targets, and optimizing the role of muhāfiẓ to ensure that the integration of the tahfid, taḥsin and tadabur is implemented more effectively and sustainably.